Takticheskie modeli sorevnovatel'noj dejatel'nosti - Kostiukevich, V. (Science in Olympic Sport, 2017)
Methodological approaches to the analysis of competitive activity of high qualification football teams are examined. Four tactical models of play of high qualification football teams: «A», «B», «C», «D», are identified on the basis of the developed method of competitive activity control, an integrated as-sessment of technical and tactical activity, and classification of interactions between players. Each of the models is characterized by the main components of competitive activity: positional attacks, high-speed attacks, pressing; passing the ball; modes of coordinative complexity of technical and tactical actions performance; specific indicators of the integral assessment of tactical activity.